Evidence That the Anti-Inflammatory Effect of Rubiadin-1-methyl Ether Has an Immunomodulatory Context - Mohr, Eduarda Talita Bramorski; dos Santos Nascimento, Marcus Vinicius Pereira; da Rosa, Júlia Salvan; Vieira, Guilherme Nicácio; Kretzer, Iara Fabricia; Sandjo, Louis Pergaud; Dalmarco, Eduardo Monguilhott (Mediators of Inflammation, 2019)
Background. In spite of the latest therapeutic developments, no effective treatments for handling critical conditions such as acute lung injuries have yet been found. Such conditions, which may result from lung infections, sepsis, multiple trauma, or shock, represent a significant challenge in intensive care medicine. Seeking ways to better deal with this challenge, the scientific community has recently devoted much attention to small molecules derived from natural products with anti-inflammatory and immunomodulatory effects. Aims. In this context, we investigated the anti-inflammatory effect of Rubiadin-1-methyl ether isolated from Pentas schimperi, using an in vitro model of RAW 264.7 macrophages induced by LPS and an in vivo model of acute lung injury (ALI) induced by LPS. Methods. The macrophages were pretreated with the compound and induced by LPS (1 μg/mL). After 24 h, using the supernatant, we evaluated the cytotoxicity, NOx, and IL-6, IL-1β, and TNF-α levels, as well as the effect of the compound on macrophage apoptosis. Next, the compound was administered in mice with acute lung injury (ALI) induced by LPS (5 mg/kg), and the pro- and anti-inflammatory parameters were analyzed after 12 h using the bronchoalveolar lavage fluid (BALF). Results. Rubiadin-1-methyl ether was able to inhibit the pro-inflammatory parameters studied in the in vitro assays (NOx, IL-6, and IL-1β) and, at the same time, increased the macrophage apoptosis rate. In the in vivo experiments, this compound was capable of decreasing leukocyte infiltration; fluid leakage; NOx; IL-6, IL-12p70, IFN-γ, TNF-α, and MCP-1 levels; and MPO activity. In addition, Rubiadin-1-methyl ether increased the IL-10 levels in the bronchoalveolar lavage fluid (BALF). Conclusions. These findings support the evidence that Rubiadin-1-methyl ether has important anti-inflammatory activity, with evidence of an immunomodulatory effect.